Hydrostatic and [001] uniaxial pressure on anatase TiO2 by periodic B3LYP-D* calculations - Albuquerque, Anderson R. [UNESP]; Maul, Jefferson [UNESP]; Longo, Elson [UNESP]; Dos Santos, Iêda M. G.; Sambrano, Julio R. [UNESP] (American Chemical Society (ACS), 2013)
The effect of high hydrostatic and [001] uniaxial pressures on TiO 2 anatase was studied under the framework of periodic calculations with the inclusion of DFT-D2 dispersion potential adjusted for this system (B3LYP-D*). The role of dispersion in distorted unit cells was evaluated in terms of lattice parameters, elastic constants, equation of state, vibrational properties, and electronic properties (band structure and density of states). A more reliable description at high pressures was achieved because the B3LYP-D* presented an improvement in all properties for undistorted bulk over conventional B3LYP and B3LYP-D. From density of states analysis, we observed that the contribution of crystalline orbitals to the edge of valence and conduction bands changed within applied pressure. The studied distortions can give some insight into behavior of electronic and structural properties due to local stress in anatase bulk from doping, defects, and physical tensions in nanometric forms. © 2013 American Chemical Society.
Keywords: Applied pressure; Density of state; Density-of-states analysis; Electronic and structural properties; Equation of state; Periodic calculations; Uniaxial pressures; Vibrational properties; Dispersions; Electronic properties; Equations of state; Hydraulics; Hydrodynamics; Titanium dioxide